Pengembangan Media Edukasi E-booklet terhadap Peningkatan Pengetahuan dan Sikap dalam Pencegahan Obesitas Siswa SMA - Wirawan, Susilo; Hermalia Putri, Dinda; -, Waluyo (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2025)
Adolescent obesity is a complex health issue characterized by excessive fat accumulation and is associated with various non-communicable diseases such as diabetes mellitus, hypertension, and cardiovascular disease. WHO (2022) reported that over 390 million children and adolescents aged 5–19 were overweight. In Indonesia, the prevalence is 3,3%, with higher rates in Yogyakarta (5,6%) and Sleman Regency (7,35%). Lack of nutritional knowledge and poor attitudes among adolescents are key risk factors. Digital educational media such as e-booklet are needed to raise awareness about early obesity prevention. The objective of this study is to determine the effect of developing e-booklet educational media on improving knowledge and attitudes in obesity prevention among high school students. This type of research is quasi-experimental design with a pretest-posttest and control group. The subjects were students at SMA Negeri 1 Godean, divided into an intervention group (lecture + e-booklet) and a control group (lecture only). Measurements were taken before and after the is intervention, with two posttests (on the same day and 7 days after). Data were analyzed using univariate and bivariate tests. There was a significant increase in knowledge and attitudes in both groups (p-value = 0,001; 0,05). Nutrition education with lectures and e-booklet media was effective in improving knowledge (p = 0,001). oth media-assisted and non- media lectures were equally effective in improving attitudes (p = 0,122; p0,05). Nutrition education using e-booklet media significantly influenced knowledge and attitudes. Lectures with e-booklet media were more effective in increasing students’ knowledge about obesity prevention.